Practical Implementation and Stability Analysis of ALOHA‐Q for Wireless Sensor Networks. Issue 5 (1st October 2016) - Kosunalp, Selahattin; Mitchell, Paul Daniel; Grace, David; Clarke, Tim
Abstract : This paper presents the description, practical implementation, and stability analysis of a recently proposed, energy‐efficient, medium access control protocol for wireless sensor networks, ALOHA‐ Q, which employs a reinforcement‐learning framework as an intelligent transmission strategy. The channel performance is evaluated through a simulation and experiments conducted using a real‐world test‐bed. The stability of the system against possible changes in the environment and changing channel conditions is studied with a discussion on the resilience level of the system. A Markov model is derived to represent the system behavior and estimate the time in which the system loses its operation. A novel scheme is also proposed to protect the lifetime of the system when the environment and channel conditions do not sufficiently maintain the system operation.